Rapamycin and the transcription factor C/EBPβ as a switch in osteoclast differentiation: implications for lytic bone diseases - Smink, Jeske J. (Springer-Verlag, 2009)
Lytic bone diseases and in particular osteoporosis are common age-related diseases characterized by enhanced bone fragility due to loss of bone density. Increasingly, osteoporosis poses a major global health-care problem due to the growth of the elderly population. Recently, it was found that the gene regulatory transcription factor CCAAT/enhancer binding protein beta (C/EBPβ) is involved in bone metabolism. C/EBPβ occurs as different protein isoforms of variable amino terminal length, and regulation of the C/EBPβ isoform ratio balance was found to represent an important factor in osteoclast differentiation and bone homeostasis. Interestingly, adjustment of the C/EBPβ isoform ratio by the process of translational control is downstream of the mammalian target of rapamycin kinase (mTOR), a sensor of the nutritional status and a target of immunosuppressive and anticancer drugs. The findings imply that modulating the process of translational control of C/EBPβ isoform expression could represent a novel therapeutic approach in osteolytic bone diseases, including cancer and infection-induced bone loss.